Stroke Rehabilitation and Patients with Multimorbidity: A Scoping Review Protocol. Issue 1 (2015) - Nelson, Michelle L.A.; Kelloway, Linda; Dawson, Deirdre; McClure, J. Andrew; McKellar, Kaileah A.; Menon, Anita; Munce, Sarah; Ronald, Kara; Teasell, Robert; Wasdell, Michael; Lyons, Renee F.
Stroke care presents unique challenges for clinicians, as most strokes occur in the context of other medical diagnoses. An assessment of capacity for implementing "best practice" stroke care found clinicians reporting a strong need for training specific to patient/system complexity and multimorbidity. With mounting patient complexity, there is pressure to implement new models of healthcare delivery for both quality and financial sustainability. Policy makers and administrators are turning to clinical practice guidelines to support decision-making and resource allocation. Stroke rehabilitation programs across Canada are being transformed to better align with the Canadian Stroke Strategy's Stroke Best Practice Recommendations. The recommendations provide a framework to facilitate the adoption of evidence-based best practices in stroke across the continuum of care. However, given the increasing and emerging complexity of patients with stroke in terms of multimorbidity, the evidence supporting clinical practice guidelines may not align with the current patient population. To evaluate this, electronic databases and gray literature will be searched, including published or unpublished studies of quantitative, qualitative or mixed-methods research designs. Team members will screen the literature and abstract the data. Results will present a numerical account of the amount, type, and distribution of the studies included and a thematic analysis and concept map of the results. This review represents the first attempt to map the available literature on stroke rehabilitation and multimorbidity, and identify gaps in the existing research. The results will be relevant for knowledge users concerned with stroke rehabilitation by expanding the understanding of the current evidence.